Running with scissors : a memoir - Burroughs, Augusten (New York : St. Martin$1 (Bs Press,s, 2002)
True story of a boy whose mother gave him away to be raised by a psychiatrist. He had to survive a bizarre household where there were no rules.
Keywords: Burroughs, Augusten -- Childhood and youth; Burroughs, Augusten -- Homes and haunts -- Massachusetts -- Amherst; Novelists, American -- 20th century -- Biography; Amherst (Mass.) -- Social life and customs; Amherst (Mass.) -- Intellectual life